2010
DOI: 10.1016/j.taap.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic influences of low-dose bisphenol A in primary human breast epithelial cells

Abstract: Substantial evidence indicates that exposure to bisphenol A (BPA) during early development may increase breast cancer risk later in life. The changes may persist into puberty and adulthood, suggesting an epigenetic process being imposed in differentiated breast epithelial cells. The molecular mechanisms by which early memory of BPA exposure is imprinted in breast progenitor cells and then passed onto their epithelial progeny are not well understood. The aim of this study was to examine epigenetic changes in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 46 publications
(57 reference statements)
2
65
0
2
Order By: Relevance
“…An increase in DNA methylation in the promoter regions of lysosomal‐associated membrane protein 3 (LAMP3) was observed both in human primary epithelial cells and breast cancer cells after exposure to low‐dose BPA, indicating that epigenetic regulation is a crucial mechanism of BPA's carcinogenic effects 140. Moreover, it was suggested that BPA‐induced changes in expression levels of microRNAs (a mode of epigenetic regulation) in placental cells might account for abnormal mammary gland architecture following fetal exposure to BPA 141.…”
Section: Mechanisms Underlying Bpa‐stimulated Carcinogenic Effectsmentioning
confidence: 99%
“…An increase in DNA methylation in the promoter regions of lysosomal‐associated membrane protein 3 (LAMP3) was observed both in human primary epithelial cells and breast cancer cells after exposure to low‐dose BPA, indicating that epigenetic regulation is a crucial mechanism of BPA's carcinogenic effects 140. Moreover, it was suggested that BPA‐induced changes in expression levels of microRNAs (a mode of epigenetic regulation) in placental cells might account for abnormal mammary gland architecture following fetal exposure to BPA 141.…”
Section: Mechanisms Underlying Bpa‐stimulated Carcinogenic Effectsmentioning
confidence: 99%
“…A stock solution of AG1478 was produced in DMSO at 20 mM/l and then diluted with phenol red-free 1640 medium to a final working solution at 10 µM. MCF-7 cells were seeded in 6-well plates at 1x10 6 cells/well and 96-well plates at 5000 cells/well. BPA and AG1478 were added at the working concentrations, respectively, to 96-well plates with five repeats for each group.…”
Section: Stat3 Sirna5 Interference Efficiency Assay Mcf-7 Cellsmentioning
confidence: 99%
“…Neonatal exposure to BPA is associated with higher body weight, increased breast and prostate cancer incidence and altered reproductive function (5). Experimental evidence indicates that exposure to BPA during childhood increases the risk of breast cancer in the adult female (6). As a consequence of this widespread opportunity for exposure, 95% of Americans carry detectable levels of BPA (7), which is currently one of the highest volume chemicals produced in the world (8).…”
Section: Introductionmentioning
confidence: 99%
“…In examination of epigenetic changes in breast epithelial cells treated with low-dose BPA and the effect of BPA on the ER-α signalling pathway and global gene expression profiles, 170 genes with similar expression changes in response to BPA were identified, and the gene suppression by BPA was mediated in part through an ER-α dependent pathway [134]. Administration of BPA to mice confirmed that DNA adducts are formed in target mammary cells (4.7-fold higher than in controls) [135].…”
Section: Bisphenol Amentioning
confidence: 99%